Midwifery assessment and interventions protocol for adolescent pregnancy: a Delphi method approach - Susanti, Dewi; Yuda, Rahmi Andrita; Handayani, Sri; Sirait, Reni Aprinawaty; Sinambela, Megawati; Yusefni, Elda (MEDISAINS, 2024)
Background: Adolescence pregnancy poses risks for both mothers and infants, often due to insufficient prenatal care resulting from societal stigmatization and lack of awareness. Around 16 million adolescents aged 15-19 years in the world give birth each year; in Indonesia, the first pregnant women aged <20 years are 45.10%, while in West Sumatra, it is 33.7%. To address this issue, integrated programs and midwifery care have been implemented. However, providing such care to adolescent mothers comes with its own set of challenges.Purpose:  This study aims to conduct a midwifery assessment and intervention protocol for adolescent pregnancy.Method: Qualitative approach The Delphi method involved two rounds of evaluation, with twenty-one participants who were independent practice midwives, six midwives involved in the mother and child health program, and nine midwifery lecturers from accredited educational institutions A (excellent). Participants had at least five years of clinical experience and were selected using purposive non-probability sampling. Participants evaluated statements related to midwifery care during the Delphi process. The validity of these statements was determined by participants providing a minimum score of 3, and the Content Validity Ratio (CVR) was calculated. Statements with a CVR greater than 0.8 were considered valid.Results: Based on expert consensus, important assessments for adolescent pregnant women include addressing issues of gender equality and domestic violence, reproductive and sexual health, risks associated with smoking and substance abuse, maintaining a healthy pregnancy, and adequately preparing for labor and parenthood.Conclusion: Midwifery management and midwifery information were deemed valid dimensions of midwifery care; relational care had one invalid item.